Formulation and development of functionally enriched onion (Allium cepa) bread. (2021) - Balakrishnaraja, R.; Swetha, V.; Srivigneswar, S.; Sakthi Priyaa, S.S.; Gowrishankar, L.
Abstract: Allium cepa also known as onion which belongs to the Amaryllidaceae is used to substitute refined wheat flour in the form of powder in bread. The product is prepared in the ratio 1:1. Onion powder is used up to 5%. We have estimated the dietary fiber content, ash content, moisture content, textural properties, gluten content and even water activity as 7.5%, 0.0931, 365.41, the texture is soft and has springiness, 3.6, 0.814. Most of the properties were found to be decreasing as the amount of onion powder was increased. Onion powder was substituted in bread to enhance its nutritional and health aspects including antimicrobial and anti-diabetic properties. Further the sensory analysis as taken in hedonic scale for flavor, texture, color, appearance, and biocompatibility.